A mouse model and 19F NMR approach to investigate the effects of sialic acid supplementation on cognitive development - Chung, Youngran; Mohanakrishnan, Raagav; Brossmer, Reinhard; Gong, Qizhi; Lönnerdal, Bo; Jue, Thomas (FEBS letters, 2020)
Researchers have observed that a sialic acid (Sia)-supplemented neonatal diet leads to improved cognition in weanling piglets. However, whether cognitive improvement appears with different physiological backgrounds and persists into adulthood is not known. Here, we have established a convenient mouse model and used an 19F NMR approach to address these questions, test the conditionally essential nutrient hypothesis about Sia supplementation, and assess the prospect of measuring Sia metabolism directly in vivo. Indeed, the neonatal mouse brain uptakes more Sia than the adult brain, and Sia supplementation of neonatal mice improves the cognitive performance of adult mice. The non-invasive 19F NMR approach and viable mouse model opens unique opportunities for clarifying the interplay of nutritional supplementation, metabolism, and cognitive development.
Available online 3 August 2019
Gesehen am 23.04.2020